Intraoperative Flurbiprofen Treatment Alters Immune Checkpoint Expression in Patients Undergoing Elective Thoracoscopic Resection of Lung Cancer - Hu, Ji-cheng (Med Princ Pract, 2020)
OBJECTIVES: This study aimed to determine the effect of intraoperative administration of flurbiprofen on postoperative levels of programmed death 1 (PD-1) in patients undergoing thoracoscopic surgery. MATERIALS AND METHODS: In this prospective double-blind trial, patients were randomized to receive intralipid (control group, n = 34, 0.1 mL/kg, i.v.) or flurbiprofen axetil (flurbiprofen group, n = 34, 50 mg, i.v.) before induction of anesthesia. PD-1 levels on T cell subsets, inflammation, and immune markers in peripheral blood were examined before the induction of anesthesia (T(0)) and 24 h (T(1)), 72 h (T(2)), and 1 week (T(3)) after surgery. A linear mixed model was used to determine whether the changes from baseline values (T(0)) between groups were significantly different. RESULTS: The increases in the percentage of PD-1((+))CD8((+)) T cells observed at T(1) and T(2) in the control group were higher than those in the flurbiprofen group (T(1): 12.91 ± 1.65 vs. 7.86 ± 5.71%, p = 0.031; T(2): 11.54 ± 1.54 vs. 8.75 ± 1.73%, p = 0.004), whereas no differences were observed in the changes in the percentage of PD-1((+))CD4((+)) T cells at T(1) and T(2) between the groups. Moreover, extensive changes in the percentage of lymphocyte subsets and inflammatory marker concentrations were observed at T(1) and T(2) after surgery and flurbiprofen attenuated most of these changes. CONCLUSIONS: Perioperative administration of flurbiprofen attenuated the postoperative increase in PD-1 levels on CD8((+)) T cells up to 72 h after surgery, but not after this duration. The clinical relevance of changes in PD-1 levels to long-term surgical outcome remains unknown.